Optogenetic Hyperpolarization of Cardiomyocytes Terminates Ventricular Arrhythmia - Funken, Maximilian; Malan, Daniela; Sasse, Philipp; Bruegmann, Tobias (Frontiers in Physiology, 2019)
Cardiac defibrillation to terminate lethal ventricular arrhythmia (VA) is currently performed by applying high energy electrical shocks. In cardiac tissue, electrical shocks induce simultaneously de- and hyperpolarized areas and only depolarized areas are considered to be responsible for VA termination. Because electrical shocks do not allow proper control over spatial extent and level of membrane potential changes, the effects of hyperpolarization have not been explored in the intact heart. In contrast, optogenetic methods allow cell type-selective induction of de- and hyperpolarization with unprecedented temporal and spatial control. To investigate effects of cardiomyocyte hyperpolarization on VA termination, we generated a mouse line with cardiomyocyte-specific expression of the light-driven proton pump ArchT. Isolated cardiomyocytes showed light-induced outward currents and hyperpolarization. Free-running VA were evoked by electrical stimulation of explanted hearts perfused with low K+ and the KATP channel opener Pinacidil. Optogenetic hyperpolarization was induced by epicardial illumination, which terminated VA with an average efficacy of 55%. This value was significantly higher compared to control hearts without illumination or ArchT expression (p=0.0007). Intracellular recordings with sharp electrodes within the intact heart revealed hyperpolarization and faster action potential upstroke upon illumination, which should fasten conduction. However, conduction speed was lower during illumination suggesting enhanced electrical sink by hyperpolarization underlying VA termination. Thus, selective hyperpolarization in cardiomyocytes is able to terminate VA with a completely new mechanism of increased electrical sink. These novel insights could improve our mechanistic understanding and treatment strategies of VA termination.